Study on customers' preferred housing packages in Kubang Pasu, Kedah - Mohammed, Asem Omar; Ng, Sen Cheng; Pee, Zhi Jun; Soon, Yaying; Low, Li Ling; Ahmad, Azhar (2015)
The purpose of having this study is to understand about the UUM lecturers‟ preferences toward the types of housing packages provided by the housing developers in Kubang Pasu, Kedah.In addition to that, the study analyses the gap between the offerings and the preferences.Besides using a survey to gather respondents‟ perceptions, this research also employs key persons‟ perspectives into the analysis.It is expected that the findings could contribute toward greater understanding in view of housing industry. This research is also expected to provide good insights on managerial applications.